2019
DOI: 10.3892/mmr.2019.10416
|View full text |Cite
|
Sign up to set email alerts
|

RIPK3 mediates renal tubular epithelial cell apoptosis in endotoxin‑induced acute kidney injury

Abstract: Renal tubular epithelial cell apoptosis is an important pathological mechanism of septic acute kidney injury (AKI). Endotoxin, also known as lipopolysaccharide (LPS), has a key role in septic AKI and can directly induce tubular epithelial cell apoptosis. The upregulation of receptor-interacting protein kinase 3 (RIPK3) in tubular epithelial cells has been reported in septic AKI, with RIPK3 mediating apoptosis in several cell types. In the present study, the effect of RIPK3 on endotoxin-induced AKI was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 51 publications
3
26
0
Order By: Relevance
“…We observed higher urinary RIPK3 in patients with sepsis. It was further confirmed that RIPK3 inhibition reduced endotoxin-(in vivo) or lipopolysaccharide (in vitro)-induced tubular cell apoptosis [30]. The apoptotic and necroptotic pathways of cell death converge at the mitochondria.…”
Section: Sepsis-induced Akimentioning
confidence: 72%
“…We observed higher urinary RIPK3 in patients with sepsis. It was further confirmed that RIPK3 inhibition reduced endotoxin-(in vivo) or lipopolysaccharide (in vitro)-induced tubular cell apoptosis [30]. The apoptotic and necroptotic pathways of cell death converge at the mitochondria.…”
Section: Sepsis-induced Akimentioning
confidence: 72%
“…An important effect associated with oxidative damage is that the renal tubular epithelial cells are the first involved in acute renal injury ( 16 , 17 ). Emerging evidence indicates that miR-30a-5p acts as a suppressor for cancer, regulating the growth, migration, and invasion of various tumors, including maintaining renal function during acute renal injury ( 18 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pleiotropic cytokine TNF-α has a particular role in the initiation of cell-survival signaling molecules such as upregulation of anti-apoptotic molecules Bcl-2, and survivin (an inhibitor of apoptosis—IAP) through activation of nuclear factor-kappa (NF-κB) [ 5 ]. In addition to the severe inflammatory syndrome, LPS activates Toll-like receptor 4 (TLR4) that is present in the membrane of immune cells and renal tubular epithelial cells, triggering the excessive release of proinflammatory cytokines, oxidative stress, and tubular cell apoptosis [ 3 , 6 ]. Severe tubular cell apoptosis plays an important role in LPS-induced AKI, showing caspase-3-positivity in tubular epithelial cells even at the early phase of AKI [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%